A Formal Model of Optimum Currency Areas - Bayoumi, Tamim (IMF Working Papers; Working Paper, 1994)
A model of optimum currency areas is presented using a general equilibrium model with regionally differentiated goods. The choice of a currency union depends upon the size of the underlying disturbances, the correlation between these disturbances, the costs of transactions across currencies, factor mobility across regions, and the interrelationships between demand for different goods. It is found that, while a currency union can raise the welfare of the regions within the union, it unambiguously lowers welfare for those outside the union.